Cardiovascular Medication and Health Service Use in Individuals With Cancer: A Retrospective Population‐Based Cohort Study - Jin Quan Eugene Tan; Huah Shin Ng; Richard Woodman; Bogda Koczwara (Cancer Medicine, 2025)
ABSTRACT Background Cancer and cardiovascular disease (CVD) frequently coexist, but little is known about CVD medication use in cancer survivors. The aim of this study was to compare CVD medication and medical service use between individuals with and without cancer. Methods Retrospective cohort study linking Australian National Health Survey 2020–2021 data from participants aged ≥ 25 years to medication dispensing, medical services, and death registry data via the Multi‐Agency Data Integration Project. Logistic regression was used to compare patterns of CVD medication use between cancer and non‐cancer groups and negative binomial regression to examine patterns of medical service utilisation by cancer and CVD status. Results The analysis included 1828 individuals with a history of cancer (cancer survivors) and 7505 people without cancer. Although cancer survivors had a higher prevalence of CVD (31% vs. 13%) compared to people without cancer, there was no difference in the adjusted use of CVD medications (adjusted odds ratios: 1.15; 95% CI = 1.00–1.33) between these two groups. There was, however, an increased rate of health service use in those with cancer alone (adjusted rate ratios (aRR): 1.39; 95% CI = 1.29–1.50), those with CVD alone (aRR: 1.71; 95% CI = 1.63–1.80), and those with both conditions (aRR: 2.10; 95% CI = 1.97–2.25) compared to people without cancer or CVD. Conclusions Despite having a higher prevalence of CVD and higher health service utilisation, the overall use of CVD medication did not differ between people with and without cancer. Cancer survivors with CVD had a higher rate of medical services use compared with persons with either condition alone or neither condition. Further research should explore the underlying reasons behind these data to inform strategies to mitigate the detrimental effects of comorbid CVD in cancer.